Building with earth : design and technology of a sustainable architecture - Minke, Gernot (Birkhäuser, 2013)
The revised 3rd edition of this handbook offers a practical systematic overview of the many uses of earth and techniques for processing it. Its properties and physical characteristics are described in informed and knowledgeable detail. The author's presentation reflects the rich and varied experiences gained over thirty years of building earth structures all over the world. Numerous photographs of construction sites and drawings show the concrete execution of earth architecture.